2020
DOI: 10.21203/rs.3.rs-22839/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Natural compounds as potential inhibitors of novel coronavirus (COVID-19) main protease: An in silico study

Abstract: COVID-19 pandemic, a novel coronavirus disease is caused by severe acute respiratory syndrome corona virus, SARS-CoV-2. It was first reported in Wuhan, China and has now expanded to more than 190 countries across the world. Till date, there is no specific medication available to prevent or target SARS CoV-2 infection. Very recently, the crystal structure of COVID-19 main protease (M pro ) was revealed by Liu et al. (2020). SARS-CoV-2 main protease (M pro ) is a key enzyme that plays a crucial role in viral rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 16 publications
(20 reference statements)
0
17
0
Order By: Relevance
“…Similarly, Mishra et al. ( 2020 ) also revealed that amentoflavone made strongest interaction with the SARS-CoV2 main protease (–9.13 kcal/mol). In a 10 ns MD simulation they have reported that the peak RMSF was observed in amino acid residue-106, 181, 46 and 151 which is different from our findings.…”
Section: Discussionmentioning
confidence: 74%
“…Similarly, Mishra et al. ( 2020 ) also revealed that amentoflavone made strongest interaction with the SARS-CoV2 main protease (–9.13 kcal/mol). In a 10 ns MD simulation they have reported that the peak RMSF was observed in amino acid residue-106, 181, 46 and 151 which is different from our findings.…”
Section: Discussionmentioning
confidence: 74%
“…Molecular interactions between SARS-CoV-2 3CL pro and natural compounds were also analyzed through docking and molecular dynamics (MD) simulation. Amentoflavone and puerarin were considered to be potential protease inhibitors [ 102 ]. In addition, computer-aided method can be adopted to design inhibitors, and several small-molecule compounds have been designed [ 103 , 104 ].…”
Section: Strategies Applied In Developing Protease Inhibitormentioning
confidence: 99%
“…However, among them, amentoflavone from Torreyanucifera plant showed highest binding energy of −10.0 kcal/mol with the SARS-COV2 main protease and further In vitro and In Vivo studies are required to understand the underlying molecular mechanisms and signaling pathways involved in SARS-COV2 main protease inhibition. In the literature, there are reports based on insilico studies that the amentoflavone can act as a potential inhibitor of SARS-CoV2 (Mishra et al., 2020 ). Furthermore, we performed molecular dynamics simulations and free energy calculations on the top five compounds to validate our findings from the molecular docking procedure.…”
Section: Discussionmentioning
confidence: 99%